Shakespeare and the Renaissance Concept of Honor - Watson, Curtis Brown (Princeton University Press, 2015)
Presenting a background study of honor, the author compares ancient concepts with the sympathetic restatements of them that appeared during the Renaissance. He places Shakespeare’s plays in the context of these Renaissance ideas, pointing up the sharp conflict between Christian morality and the revived pagan humanism. He demonstrates by pertinent evidence from the plays that Shakespeare favored humanist values over Christian values.Originally published in 1960.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905
Description based on online resource; title from PDF title page (publisher's Web site, viewed Sep. 08, 2016)
Keywords: Shakespeare, William -- 1564-1616; Honor in literature; Honor; Renaissance -- England; Begriff; Ehre